Peningkatan Produksi Garam Beryodium Melalui Aplikasi Alat Pencetak Garam Secara Mekanik - Handayani, Dwi; Murni, Murni; Ikhsan, Diyono; Arifan, Fahmi (Universitas Diponegoro, 2011)
The salt moulder groups